Analisis Efektivitas Pemasaran Online dan Offline pada Penjualan Mobil Bekas di Showroom Yuna Mobil Rantau Prapat - Rahmatika Pertiwi Matondang; Hafiza Adlina; Onan Marakali Siregar (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effectiveness of online and offline marketing strategies in increasing used car sales at Yuna Mobil Showroom Rantau Prapat. The research background is based on the rapid development of information technology and digitalization, which encourage businesses to combine conventional and digital marketing strategies to reach a wider range of consumers. This research employed a descriptive qualitative method with data collection techniques including observation, in-depth interviews, documentation, and triangulation. The results indicate that online marketing plays a significant role in building brand awareness, expanding market reach, and providing fast and efficient access to information through social media, marketplaces, and instant messaging applications. However, this strategy has not been fully effective in converting consumer interest into actual purchase decisions, as customers still require direct product experience. Conversely, offline marketing is proven to be more effective at the decision-making stage due to direct interaction, test drives, and higher consumer trust in the actual condition of used cars. Therefore, the effectiveness of marketing will be optimized if online and offline strategies are implemented in an integrated and complementary manner. This study provides practical contributions for automotive business players in designing marketing strategies aligned with local consumer characteristics, as well as academic contributions to the development of marketing management studies in the digital era.